Brucella ovis: InvasãO, tráfego, fatores de virulência e resposta imune - De Paula Antunes, João Marcelo Azevedo [UNESP]; Megid, Jane [UNESP] (Universidade Estadual de Londrina, 2013)
Brucellosis remains an economic problem in animals and public health. Worldwide ovine brucellosis caused by Brucella ovis is considered a major cause of infertility in sheep. The factors responsible for persistence of the agent are not known, as well as the mechanisms involved in immune defense and possibly the persistence of the agent. Brucella spp. induces moderate inflammatory response. The nature of the intracellular agent stimulates immune response of the type 1 helper T lymphocytes. Studies of the pathogenesis of ovine brucellosis are scarce. Recent developments have shown that the inflammatory response induced by moderate brucelas represent probably the result of an attempt to escape the immune response and suppression of host immune response. Were reviewed by the mechanisms described by brucelas and Brucella ovis for penetration into the host, escape of the immune response and the immune response generated by the infection.
Brucella ovis: Invasion, traffic, virulence factors and immune response
Keywords: Brucella ovis; Brucellosis; Immunopathology; Pathogenesis